Solidarity of the (Non)Initiates. Women’s Literary Evenings in 1930, 1935 and 1938 - Cesiulė, Agnė (Colloquia, 2024)
The article examines the Women’s Literary Evenings organized by the female members of the organization Ateitis and the magazine Naujoji vaidilutė in 1930, 1935 and 1938, using the sources of public discourse, i.e., reviews of those evenings published in daily newspapers and cultural press. The article takes into account the study carried out by other researchers of that time and the controversies surrounding women’s participation in culture during the 1930s. I analyze the process using a sociological approach to literature and methodological tools from Pierre Bourdieu’s theory on the field of cultural production, which treats the group of women as a limited and non-independent group of participants in the literary field. The article explores the transformations that have taken place in Women’s Literary Evenings over time: the development of those events, the changes in the concept, the reactions of participants and organizers to criticism, and its consequences. It also discusses the changes of the concept of women as writers and the possibilities of their initiation as writers during the period in question (eight years).
Keywords: moterų literatūros vakaras; literatūros sociologija; moterų solidarumas